The Importance of Philosophy of Science of Logic: Al-Farabi's Conception and Its Application on Tertiary Education - Mohammed Hussein Boayo, Suleiman (s.n, 2012)
The purpose of this study is to attempt to clarify the importance of science of logic in Al-Farabi conception and its elation to the tertiary education, and to come out with method that should be employed in teaching logic. I will also explain the applicability of these methods. This may encourage students to see its importance in their education. The scope of the study will mainly focus on Al-Farabi's conception of the science of logic.